2019
DOI: 10.1017/laq.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Community Identity and Shared Practice at Actuncan, Belize

Abstract: Shared identities create deep historical ties to community spaces and can facilitate or constrict political expansion. This research examines the relationship between the ways in which families engaged local landscapes and developed shared identities at Actuncan, Belize, during the Terminal Classic period, a time when the city experienced population growth as surrounding centers declined. The nature and location of activity patterns in and around three residential groups allow inferences about shared practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The partial leaching of soils using diluted HCl (e.g., Wells, 2004) or a mixture of diluted HNO 3 and HCl acids (Aqua Regia) has been the most common method used in the Maya soil literature to date. LeCount et al (2016) and Fulton (2019) reported that their results using partial digestion methods showed ". .…”
Section: Mercury Analytical Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…The partial leaching of soils using diluted HCl (e.g., Wells, 2004) or a mixture of diluted HNO 3 and HCl acids (Aqua Regia) has been the most common method used in the Maya soil literature to date. LeCount et al (2016) and Fulton (2019) reported that their results using partial digestion methods showed ". .…”
Section: Mercury Analytical Approachesmentioning
confidence: 99%
“…Most of these contexts were Late Classic age, though a smaller number of floor areas sampled were from the earliest history of the site, from the Terminal Preclassic and Early Classic periods. Second, Fulton (2019) reported the results of inorganic chemical analysis of 703 on-site soils samples collected across Group 1 (Late to Terminal Classic occupation areas), Group 5 (Operation 47), Group 6 (Operation 46), and from excavated spaces between architecture (Operation 48), and also eight off-site control samples.…”
Section: Actuncanmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 7 grew haphazardly around a wide patio, indicating that its structures were either distinctly different in function or were the homes of incongruent social entities. Group 6 may have functioned as a Late Classic special-function building (Fulton 2015). Unlike other nearby patio-focused groups, it was constructed predominantly of perishable materials, and little plaster was found on platform floors.…”
Section: Actuncan: a Long-lived Mopan River Valley Centermentioning
confidence: 99%
“…Ruling families likely fled (or died) and poor populations chose to leave. Like the longest occupied households in the surrounding hinterlands, the households at Actuncan were deeply rooted, and their members chose to remain at the site through the Terminal Classic period (Fulton 2019;LeCount et al 2019;Mixter et al 2014). As Xunantunich's power contracted, Actuncan initiated a renewed programme of Community Resilience and Urban Planning during the Ninth-Century Maya Collapse civic construction and ritual activity and the site's long-lived households formed the core of a new, more inclusive socio-political order that was no longer led by divine rulers (LeCount et al 2011; Mixter 2016).…”
Section: Actuncan Backgroundmentioning
confidence: 99%